Pengaruh Harga, Kualitas Pelayanan Dan Fasilitas Terhadap Kepuasan Pelanggan di Imam Bonjol Hostel Semarang - Arianto; Yunus Handoko; Widi Dewi (Bursa : Jurnal Ekonomi dan Bisnis, 2023)
Current technological developments make hotel business competition very tight, so the hotel manager must be able to provide the best service so that customer satisfaction can be achieved. Customer satisfaction is the difference between expectations and perceived performance or service. Imam Bonjol Hostel Semarang is a hotel that offers cheap prices with facilities that are not much different from its competitors. However, due to the Covid-19 Pandemic that has hit evenly to various countries, it has had a major impact on hotel visitors in recent years. Based on data, visitors to Imam Bonjol Hostel in 2020 decreased by around 10 to 20 consumers per week. The decline was caused by many factors, one of which was customer satisfaction which decreased drastically. In this study, the factors that influence customer satisfaction were analyzed through price, quality of service, and facilities. The purpose of this study is to analyze the effect of price, quality of service, and facilities on customer satisfaction at Imam Bonjol Hostel. The population in this study were customers of Imam Bonjol Hostel. The sample in this study was 100 customers. The sampling technique in this study was carried out with the Purposive Sampling technique. The data type is primary. Data collection methods using questionnaires. The analysis technique used is multiple linear regression. The results of the analysis using SPSS show that: Competitive prices affect customer satisfaction. Service quality affects customer satisfaction. Facilities affect customer satisfaction